Hamil Diluar Nikah Sebagai Alasan Dispensasi Kawin Di Pengadilan Agama Koto Baru Solok (Studi Penetapan Perkara Nomor 119/PDT.P/2020/PA.KBR) - Rahmad, Abd.; Oktavia, Monica (Fakultas Hukum Universitas Tamansiswa Padang, 2023)
According to Article 7 Paragraph (2) of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, it is stated that: